Binary ethanol-water solvents affect betalain contents and health-promoting properties of red Celosia argentea inflorescence extracts - Thiyajai P. (2023)
The present work aimed to compare the betalain profiles and contents in the red inflorescence of Celosia argentea extracts obtained using different ethanol-water ratios. The impact of betalain content on the health-promoting properties was also evaluated. Freeze-dried inflorescence powder was extracted three times with aqueous-ethanol (0, 20, 40, 60, and 80% (v/v) ethanol). The highest total betacyanin content was found in the 40 and 60% aqueous-ethanolic extracts. Total phenolic content and antioxidant activities of the extracts increased with increasing ethanol concentration. The antioxidant activities measured by oxygen radical absorbance capacity (ORAC) assay of the 60 and 80% aqueous-ethanolic extracts were significantly higher than that of ascorbic acid. The IC50 of α-glucosidase inhibitory activities of all extracts were comparable to that of acarbose. Phenolics were the major responsible compounds for antioxidant (r = 0.975, p < 0.01 by ORAC assay), α-amylase (r = -0.725, p < 0.01), and lipase (r = 0.607, p < 0.05) inhibitory activities, whilst betacyanins corresponded to α-glucosidase inhibitory activities (r = 0.627, p < 0.05). The 60% aqueous-ethanolic extract was superior to the others in terms of colour, phytochemical contents, and health-promoting activities. These extracts can be utilised as natural food colorant, functional ingredients, and nutraceuticals